Impeding Nucleotide‐Binding Oligomerization Domain‐Like Receptor 3 Inflammasome Ameliorates Cardiac Remodeling and Dysfunction in Obesity‐Associated Cardiomyopathy - Shi‐qiang Liu; Sai‐yang Xie; Tong Zhang; Heng Zhang; Meng‐Ya Chen; Yun Xing; Nan Zhao; Lanlan Li; Si Chen; Sha‐sha Wang; Xiao‐feng Zeng; Wei Deng; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Inflammation and metabolic disturbances are key culprits in the pathogenesis of obesity‐associated cardiomyopathy. The NLRP3 (nucleotide‐binding oligomerization domain‐like receptor 3) inflammasome mediates the release of the proinflammatory cytokines IL‐1β (interleukin‐1β) and IL‐18 by activating caspase‐1, which is strongly implicated in metabolic disturbances. We here sought to determine whether NLRP3 inflammasome inhibition could ameliorate obesity cardiomyopathy and if so, to further explore its underlying mechanisms. Methods and Results Male mice were fed a high‐fat diet for 24 weeks to induce obesity cardiomyopathy. MCC950 was used to inhibit NLRP3 inflammasome activation. Recombinant adeno‐associated virus serotype 9 encoding TXNIP (thioredoxin‐interacting protein) under cTnT (cardiac troponin T) promoter and the mitochondrial‐targeted antioxidant MitoTEMPO were injected into obese mice to investigate the specific mechanism. To mimic obesity cardiomyopathy in vitro, neonatal rat ventricular myocytes transfected with the small interfering RNA against TXNIP were incubated with 400 μmol palmitic acid for 24 hours. NLRP3 inflammasome was significantly increased in obese hearts. NLRP3 inflammasome inhibition by NLRP3 deletion or MCC950 prevented obesity‐induced cardiac systolic and diastolic dysfunction, myocardial hypertrophy and fibrosis, and excessive lipid accumulation in male mice. Conversely, TXNIP overexpression worsened obesity‐associated cardiomyopathy. Similarly, MCC950 treatment or TXNIP knockdown reduced palmitic acid‐induced NLRP3 inflammasome activation and lipid storage. Mechanistically, abnormal NF‐κB (nuclear factor kappa B) pathway activation, increased mitochondrial reactive oxygen species, and elevated TXNIP levels led to excessive NLRP3 inflammasome activation. Conclusions Our study confirms that aberrant NLRP3 inflammasome activation in cardiomyocytes worsens obesity‐associated cardiomyopathy and implicates inhibition of NLRP3 inflammasome as a potent therapeutic approach for obesity cardiomyopathy.